Anesthesia in Cosmetic Surgery - Friedberg, Barry L (Cambridge University Press, 2013)
Anesthesiology has undergone remarkable changes in recent years. Among them is the development of anesthesia subspecialties and of anesthesiologists who focus most or all of their time in one area of anesthesia practice. This change has several advantages for patients, surgeons, and anesthesiologists. For one, the anesthesiologist learns the needs and expectations of the surgeon, which optimizes surgical outcome for patients. Furthermore, knowing what to expect, the anesthesiologist is better able to adjust both the doses and timing of drugs so that patients are adequately anesthetized for surgery but then emerge fromanesthesia in a timely and comfortable manner.Nowhere are these issuesmore important thanwhensurgery isperformedinthe ambulatory or office-based setting. Expectations are that patients undergoing surgery in these settings will go home the same day. Resources for extended care are usually nonexistent, as they should be.